Análise de pellets nas praias do litoral paulista e seus efeitos ecotoxicológicos em ambientes marinhos - Mendes, Gabriel Izar [UNIFESP] (2016)
Pellets are small grains of resin with a few millimeters (>5 mm), produced and used in large scale, that are among the most found debris in beaches all over the world. It is persistent materials and usually adsorb chemicals compounds, representing a strong harmful to the marine animals and coastal environment in general. This study aim to evaluate the pellets density in the superficial layer in beaches in São Paulo coast, trying to establish a relationship between the spatial distribution along the coast and the distance from a pellet source. We tested the hypothesis that the pellets in the superficial layer were concentrated close to the Santos port, because it is the main pellets source for the area. Then, we tested the toxicity to marine organism and some factors that contribute to this toxicity, like pellets coloration, sampling site (beach) and the density find in the São Paulo coast. To the pellets distribution, twelve beaches were selected in São Paulo coast, with different distances of Santos port. Pellets were collected in the superficial sand layer (5 cm), on the high upper beach limit, with twenty samples per beach. For the ecotoxicity assays, pellets were manually and actively collected in two beaches in two contaminated areas in different levels. These assays were tested with urchin (Lytechinus variegatus), amphipod (Tiburonella viscana) and copepod (Nitokra sp.), in acute and chronic assay. It was noted a decreasing gradient of pellets density along the São Paulo coast, both north and south of Santos port, with higher densities inside the Santos bay, where the port is located. Beyond to the port distance, several other factors may have influenced the dispersion of pellets in São Paulo coast, including environmental factors not assessed in this study, like wind and superficial currents direction and the coast geography, that seem to be a important factor to pellets dispersion in coastal areas. Pellets showed chronic toxicity for both tested organism (L. variegatus and Nitokra sp.) at extremely high densities, however, they were not capable to confer acute toxicity in densities founded in São Paulo Beaches for and literature for T. viscana. The high variability of adsorbed contaminants concentration in each pellet can be a factor with more influence for the pellet toxicity, than the pellets density factor tested in this study.